The regression analysis of predictors for selected health behaviors among elderly in Poland - Magdalena Młynarska; Grzegorz Józef Nowicki; Patrycja Misztal-Okońska; Renata Korecka; Mariusz Goniewicz; Katarzyna Naylor (Kazimierz Wielki University, 2018)
The meaning of the word health takes on a different connotation in relation to certain individuals or groups. The trend is visible when taking under consideration the health of elderly individuals or the entire population in this age category. Even more, there has been noticed a great spread in individuals belonging to this age group, given that the elderly person is considered to be one that completed 65 years of life untill the diversified its end. Therefore, such a wide age range covering approximately 20 - 30 years demands diverse criteria for persons aged 70 years and the ones aged 90 years.             The purpose of the study was to identify predictors influencing the health behaviors of people over 65 years of age in Poland.             On the one hand, older age allows a sense of satisfaction, fulfillment and understanding for the meaning of the whole past life. On the other hand, it can be a source of physical and mental pain, the cause of dissatisfaction and frustration. All in all, the manner in which this period is experienced depends on numerous factors. These include both genetic and individual factors as well as social aspects. However, the most important ones are considered to be health behaviors of seniors. For that reason, taking into account the perspective of aging Poland, joint preparation for old age should become a priority undertaking.